Augmented anticancer effect and antibacterial activity of silver nanoparticles synthesized by using Taxus wallichiana leaf extract - Aliya Yousaf; Muhammad Waseem; Aneela Javed; Sofia Baig; Bushra Ismail; Ayesha Baig; Irum Shahzadi; Shamyla Nawazish; Iftikhar Zaman (PeerJ, 2022)
Background Taxus wallichiana is an evergreen tree species found in the Himalayan region of Pakistan. The tree possesses important secondary metabolites such as Taxol that has been implicated in treating breast, ovarian and colon cancer. Therefore keeping in view the importance of this plant species, silver nanoparticles were synthesized using Taxus wallichiana aqueous leaf extract and evaluated for their anti-bacterial and anti-cancer properties. Methods Silver (Ag) nanoparticles (NPs) were characterized for their optical, morphological and structural features using techniques such as UV-visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) and were evaluated for their antibacterial activity and anti-cancer activity using U251 cell line. Results The study showed that the UV-absorbance peak of Ag2O NPs at 450 nm shifted to 410 nm, affirming the formation of leaf extract Ag NPs. Similarly structural studies revealed the crystalline nature of the cubic structure of the Ag crystal with an average crystallite size of 29 nm. FTIR analysis exhibited the existence of different functional elements including O-H and N-H and phenolic groups. Non-spherical glomerular shaped Taxus wallichiana Ag NPs were observed from SEM studies and EDX profile showed Ag as the main element along with constituent of biological origin. The synthesized Ag NPs showed significant antibacterial activity against Salmonella typhi, and Staphylococcus aureus. The cytotoxic activity of Ag NPs on U251 brain cancer cells showed a synergistic effect with 10 ug/mL concentration after 48 and 72 h incubation based on cell viability assay indicating promising glioblastoma drug potential.